2020
DOI: 10.1186/s12936-020-03419-x
|View full text |Cite
|
Sign up to set email alerts
|

Mass radical treatment of a group of foreign workers to mitigate the risk of re-establishment of malaria in Sri Lanka

Abstract: Background Following malaria elimination, Sri Lanka was free from indigenous transmission for six consecutive years, until the first introduced case was reported in December 2018. The source of transmission (index case) was a member of a group of 32 migrant workers from India and the location of transmission was their residence reporting a high prevalence of the primary vector for malaria. Despite extensive vector control the situation was highly susceptible to onward transmission if another of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Hence, this study identified the male gender to be at a higher risk to be infected with malaria unlike the female gender. Findings from this study were similar to what was reported in earlier works [26,27,28]. Table 11 showed the mean and median of the ages of the patients within the study period.…”
Section: Resultssupporting
confidence: 90%
“…Hence, this study identified the male gender to be at a higher risk to be infected with malaria unlike the female gender. Findings from this study were similar to what was reported in earlier works [26,27,28]. Table 11 showed the mean and median of the ages of the patients within the study period.…”
Section: Resultssupporting
confidence: 90%
“…The included studies encompass a wide variety of settings including countries in Asia Pacific, the Eastern Mediterranean, Africa, and Europe, and addressed control, elimination, and prevention of reestablishment of malaria. The themes of the articles were focused around appraisal of surveillance and response, [11][12][13][14][15][16][17][18] updating national policies to facilitate malaria control efforts, 17,[19][20][21] travel as a risk factor for malaria and methods to mitigate the risk, 12,13,20,[22][23][24][25][26] vector control, 12,16,27 transfusion malaria, 21,28 competing interests, 27,29,30 malaria in border areas, 15,19,22,31 and other challenges posed by 29 Nepal Elimination Competing interests Ajayi et al 32 Related to Africa Control Other emerging communicable diseases Alotaibi et al 11 Saudi Arabia Prevention of reintroduction Surveillance response Al Zahrani et al 22 Saudi Arabia-Yemen border Elimination Travel as a risk factor Border areas Chen 23 Taiwan Prevention of reintroduction Travel as a risk factor Danis et al 12 Greece Prevention of reintroduction Surveillance response Travel as a risk factor Vector control Fernando et al 30 Sri Lanka Elimination Competing interests Fernando et al …”
Section: Resultsmentioning
confidence: 99%
“…In terms of surveillance and response, Saudi Arabia focuses specifically on Hajj; Greece has high rates of immigration and focuses on controlling resurgence; and Sri Lanka focuses on maintaining vigilance, fast containment, and monitoring foreign workers. [11][12][13][14]16 Even when surveillance systems are established in countries, sometimes the processes of data collection and reporting are disorganized and incomplete. In 22 countries in the Asia Pacific region, surveillance data were incomplete and not comprehensive enough to facilitate effective responses.…”
Section: Prevention Of Reintroduction Transfusion Malariamentioning
confidence: 99%
“…Independently of the mechanisms used by the parasite, the higher investment in gametocyte production observed in this study suggest that reactive focal MDA approaches with gametocytocidic antimalarials such as primaquine, coupled with glucose-6-phosphate dehydrogenase de ciency testing, 30 may increase the impact of strategies aiming to interrupt or prevent the reestablishment of malaria transmission. 31 The results of this study are subjected to several limitations. First, Pf infections that were successfully analyzed correspond to those in the upper range of parasite densities, given the limit of detection of the transcriptional and sequencing approaches.…”
Section: Discussionmentioning
confidence: 97%